2020
DOI: 10.3390/ma13235407
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of SBR Composites Containing Graphene Nanoplatelets Modified with Pyridinium Derivative

Abstract: The goal of this work was to study the effect of graphene nanoplatelets (GnPs) modified with ionic liquid (IL) on properties of styrene–butadiene rubber (SBR) composites. GnPs were decorated with IL or were modified in bulk directly during rubber mix preparation. The ionic liquid used was 1-butyl-4-methylpyridinium tetrafluoroborate (BMPFB). The textural properties were studied to confirm surface modification of GnPs with BMPFB. In these investigations, the impact of the concentration of GnPs and the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…IMG started to degrade at a lower temperature than BMIB and showed more weight loss compared to GnP. The BMIB was adsorbed on graphene surface and the degradation of BMIB on the surface of GnPs decreases its temperature of maximum rate of degradation by 65 C. 13 This lowering in the thermal stability of IMG compared to GnP corroborates the incorporation BMIB on the surface of GnPs.…”
Section: Characterization Of Modified Graphene Nanoplatelets With Imi...mentioning
confidence: 65%
See 2 more Smart Citations
“…IMG started to degrade at a lower temperature than BMIB and showed more weight loss compared to GnP. The BMIB was adsorbed on graphene surface and the degradation of BMIB on the surface of GnPs decreases its temperature of maximum rate of degradation by 65 C. 13 This lowering in the thermal stability of IMG compared to GnP corroborates the incorporation BMIB on the surface of GnPs.…”
Section: Characterization Of Modified Graphene Nanoplatelets With Imi...mentioning
confidence: 65%
“…Even though it is difficult, the covalent and non-covalent functionalization of graphene is possible. 13 Recently, ionic liquids (ILs) having excellent chemical and thermal stability, very low vapor pressure, nonflammability, and high ionic conductivity have been marketed as "green solvents" and are used for numerous applications along with polymers. 14 ILs have been incorporated to improve the infill dispersion, mechanical and thermal properties, and ionic conductivity of elastomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaca et al added 5 phr of graphene nanoplatelets to SBR and experienced a 50% increase in elongation at break and over 100% increase in tensile strength. They achieved these results via the surface modification of graphene 44 …”
Section: Introductionmentioning
confidence: 99%
“…They achieved these results via the surface modification of graphene. 44 Malas et al demonstrated that the mechanical properties of chloroprene rubber and chlorosulphonated polyethylene rubber were significantly enhanced by the addition of up to 9 phr of graphene oxide. They reported a 35% increase in abrasion resistance and up to 400% increase in tensile strength for their nanocomposites.…”
Section: Introductionmentioning
confidence: 99%